Adaptasi Masyarakat Terhadap COVID-19 Di Desa Genting Tanah, Kecamatan Kembang Janggut, Kalimantan Timur - Yaskinul Anwar; Muhammad Farhan Maulana; Muhammad Dika Oktoberdinata; Umi Kholifatus Saniah; Risma Amelia; Rita Wulandari (JPG (Jurnal Pendidikan Geografi), 2020)
The initial appearance of the Corona Virus is thought to be pneumonia, with symptoms similar to flu in general. These symptoms include coughing, fever, fatigue, shortness of breath and no appetite. The global COVID-19 pandemic has created new problems for the nation-state, especially regarding how the state's efforts to prevent and stop the spread of this virus from spreading. Genting Tanah Village is a village located in Kembang Janggut District, Kutai Kartanegara Regency. The selection and determination of Genting Tanah Village as the research location was based on the consideration that this village was one of the villages that had never been a red zone during the pandemic. Data collection was carried out by direct survey to respondents who were at the research location. Sampling was carried out randomly, with 35 respondents from all areas of the Genting Tanah village. Data collection was carried out by directly interviewing respondents in order to obtain more valid information and to deepen the discussion. The variables used consisted of religion, education, work, income, social and economic interactions. The Covid-19 pandemic has not affected this pattern of life.